Efeito dos ácidos graxos da série w3 e w6 na regeneração de lesões cutâneas em Prochilodus lineatus - Pereira, Bruna de Castro (2017)
In intensive fish farming, fish are more susceptible to diverse lesions and serve as a gateway to pathogens, causing economic loss. Therefore, it is extremely important that tissue repair should be fast and effective for a return to homeostasis. The objective of this study was to evaluate the effect of supplementation of different fatty acid sources of the ω3 and ω6 series on performance, bromatological composition, hematological parameters and regeneration of cutaneous lesions in curimbas (Prochilodus lineatus). An experimental experiment was carried out with isoproteic, isoenergetic and isolipidic diets, with different sources of oil (fish, corn and linseed). A total of 216 animals housed in 12 tanks (250L) were used in a recirculation system, 18 fish each. The experimental design was a randomized block design consisting of three diets (oil sources) and four weight classes (blocks) per treatment. There were no significant differences (P> 0.05) between treatments for performance variables, bromatological composition and hematological parameters of the animals. It was observed that diets with fish oil and flaxseed accelerated the regeneration of cutaneous wounds, on the 7th day after induction of the lesion. The treatments with fish oil and linseed showed a reduction in the lesion area of 24 and 24.8%, respectively, in relation to treatment with corn oil. In view of the results obtained, supplementation with flaxseed oil in diets for tropical fishes is suggested, since flaxseed has great availability in relation to fish oil, being more feasible for fish farms.